Керування у педагогіці Й. Гербарта - Ірина Гоштанар (Pavlo Tychyna Uman State Pedagogical University, 2013)
У статті розглянуто науково-педагогічну спадщину видатного представника світової педагогічної науки, німецького педагога, філософа і психолога Й. Гербарта (1776-1841) у контексті розвитку шкільництва Німеччини. Особлива увага звертається на погляди вченого щодо проблеми дисциплінування молоді особистості. В статье анализируется научно-педагогическое наследие выдающегося представителя мировой педагогической науки, немецкого педагога, философа и психолога И. Гербарта (1776-1841) в контексте развития школьного образования Германии. Особое внимание обращается на взгляды ученого относительно проблемы дисциплинирования подрастающей личности. The article focuses on the scientific and pedagogical heritage of German pedagogue, philosopher and psychologist J. Herbart (1776-1841), an outstanding representative of the world pedagogical science in the context of development of scholastic education in Germany. A special attention is paid to the scientist's views on the problem of reducing to discipline a growing personality. It's stressed in the article that understanding the importance of upbringing by J. Herbart had implied priority of pedagogical guidance as observing discipline in an educational activity. J. Herbart distinguished a special kind of a pedagogical activity - a guidance, which has its own pedagogical legitimacy, because it doesn't use force towards children's will. Guidance doesn't have any intentions in relation to children's will and volition. Guidance has a double meaning in Herbart's pedagogical system: firstly guidance as «a reduction of a child's wild intemperance» (mostly it's connected with an upbringing in a family), and authority and affection are the main methods of it; secondly guidance as a reducing to discipline in school educational activity and the main method of it is «an encouragement of manifestation of the good» (development of children's best abilities). It's noted in the article that J. Herbart criticized gymnasiums of that times, which, because of their curricula, didn't develop many sided personalities, but on the one hand overloaded pupils, and on the other hand, - family tutors, who brought up children according to social division in the society. J. Herbart distinguished two ways of improving a school as a social institution: many sided education and creation of an institute of «free teachers». Performing duties of his free pedagogical activity, an educator becomes an intermediary between an upbringing in a family and school education and is way beyond the family upbringing and state educational institutions.